Aspects of health services in Sami areas - Gaski, Margrete (University of Tromsø, 2012)
Paper 3 of this thesis is not available in Munin: 3. Margrete Gaski: 'A comparative study of strategies for recruiting young Indigenous People to become physicians : nearly fifty years of preferential admission and support (accepted manuscript in Human Resources for Health) Helsepolitikk for samer har bygd på antakelser om at språk- og kulturforskjeller mellom helsepersonell og pasienter fører til et underforbruk av helsetjenester og en dårligere helsetjeneste. Første studie i denne avhandlingen analyserer forbruket av sykehus, og avviser at det er et underforbruk av helsetjenester blant samer generelt, men finner at de eldste innbyggerne i samiske kommuner er noe sjeldnere på sykehus enn eldre ellers i landet. Siden 1963 har man forsøkt å forbedre helsetjenesten i samiske kommuner gjennom samisk kvote på helsefagutdanninger. Samisk kvote på medisin skulle resultere i flere samiske leger i samiske kommuner. En sporingsstudie i denne avhandlingen stiller spørsmål ved kvoter som egnet virkemiddel til dette i dag. En sammenlignende studie fra USA, Canada, Australia og New Zealand peker på at effekter av slike kvoteordninger sjelden undersøkes. Better health service for Sami people has been lifted on the political and professional agenda for many years and from several sides. As a response on a situation with difference in health gradients between the northernmost county of Finnmark, where many Sami live, and the counties further south in Norway, government actions has been implemented since the 1960s to strengthen the Sami people. Since 1980, problems of under-utilization of health services and communication between health workers and Sami patients are brought into focus, and Sami spokesmen still claim that the health services do not ensure the needs of Sami patients. The literature concerning health services for Sami patients indicate an early conclusion that the existence of health services research in the fields of health care utilization among Sami is limited to a few studies, not very wide-ranging. Along ...